Prediction of Student Graduation Accuracy Using C45 Algorithm (Case Study: Fasilkom Unsika): Prediksi Ketepatan Kelulusan Mahasiswa Menggunakan Algoritma C45 (Studi Kasus: Fasilkom Unsika) - Dyah Ayu Wulandari; Betha Nurina Sari; Tesa Nur Padilah (Universitas Singaperbangsa Karawang, 2022)
The Faculty of Computer Science at University Singaperbangsa Karawang has had problems in the last 3 years, namely the low level of accuracy of graduation. The number of students from the 2013 batch graduated on time as many as 43 out of 349. In 2014 51 out of 343 graduated on time. In 2015 there were 79 students graduating on time or 49%. The purpose of this study is to perform data mining using the C4.5 algorithm on Weka tools to determine the classification of student graduation determination. So that research is carried out to facilitate the determination of graduation. The distribution of training and testing data is carried out in 5 categories, namely 90:10, 80:20, 70:30, 60:40, 50:50 to find out the best results from the dataset comparison category. The results of the study show that the best accuracy values ​​are 90% training data and 10% testing data with an accuracy value of 84.2% and an ROC value of 0.852. Based on the results of the highest accuracy and ROC values, so it has a better and more accurate model.